Hemodynamic responses are abnormal in isolated cervical dystonia. Issue 4 (6th November 2019) - Berman, Brian D.; Groth, Christopher L.; Shelton, Erica; Sillau, Stefan H.; Sutton, Brianne; Legget, Kristina T.; Tregellas, Jason R.
Abstract: Neuroimaging studies using functional magnetic resonance imaging (fMRI), which measures brain activity by detecting the changes in blood oxygenation levels, are advancing our understanding of the pathophysiology of dystonia. Neurobiological disturbances in dystonia, however, may affect neurovascular coupling and impact the interpretability of fMRI studies. We evaluated here whether the hemodynamic response patterns during a behaviorally matched motor task are altered in isolated cervical dystonia (CD). Twenty‐five CD patients and 25 healthy controls (HCs) underwent fMRI scanning during a paced finger tapping task (nondystonic task in patients). Imaging data were analyzed using a constrained principal component analysis—a statistical method that combines regression analysis and principal component analysis and enables the extraction of task‐related functional networks and determination of the spatial and temporal hemodynamic response patterns associated with the task performance. Data from three patients and two controls were removed due to excessive movement. No significant differences in demographics or motor performance were observed. Three task‐associated functional brain networks were identified. During task performance, reduced hemodynamic responses were seen in a sensorimotor network and in a network that included key nodes of the default mode, executive control and visual networks. During rest, reductions in hemodynamic responses were seen in the cognitive/visual network. Lower hemodynamic responses within the primary sensorimotor network in patients were correlated with the increased dystonia severity. Pathophysiological disturbances in isolated CD, such as alterations in inhibitory signaling and dopaminergic neurotransmission, may impact neurovascular coupling. Not accounting for hemodynamic response differences in fMRI studies of dystonia could lead to inaccurate results and interpretations. Abstract : Using an unaffected motor task and constrained principal component analysis, we show that hemodynamic response patterns within activated networks including the sensorimotor network differ between patients with cervical dystonia and healthy controls. Neurobiological disturbances underlying dystonia could alter the hemodynamic response and impact the reliability of functional MRI studies.